Resistive switching in metal-oxide-metal structures for non-volatile memory application - Zhang, Yu. (2012)
Underlying mechanism of metal-oxide-metal resistive switching device has been of long research interest. Several models have been proposed based different types of materials used. Recent studies showed that oxygen vacancies present at Schottky junction type metal oxide (especially Strontium Titanate) interface acting as trapping sites for electrons played an important role in adjusting barrier height thus resulting in resistance switching. Based on this model adjusting effect of oxygen vacancies on different barrier heights and further on on/off ratio was investigated in this project. Strontium Titanate with perovskite structure and work function about 4.2eV with Pt, Fe and Al metals with different but relatively deep work functions were used to form Schottky junction devices. PLD technique was employed for deposition of metal electrodes. Annealing of all STO substrates was done under same condition to dope them with certain quantity of oxygen vacancies and also optimum voltage holding time for I V characteristic measurements was determined first. It was aimed to keep barrier height as the only variable. Sweeping of voltage bias was done on every sample. The result indicated oxygen vacancies did have significant adjusting effect and more obvious on samples with larger Shottky barrier as larger on/off ratio was observed from Pt sample of supposed largest barrier height. It was also interesting that Fe sample had similar current value in both on and off state thus a similar on/off ratio to Pt sample. It might be attributed to lack of statistics and their barrier height difference was not so obvious.